Fractional Reserve Banking System and Money Multiplier Effect: A Proposed Scheme from Sharia Banking - Saratian, Eko Tama Putra; Irfan, Mohammad (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes the effects of implementing the fractional reserve requirement banking system, its impact on the money multiplier, and the solutions offered by Sharia banking. The world community is starting to care about the dangers of the three pillars and their impact on the economy. Interest, fiat money, and fractional reserves are requirements in the banking system. This must be studied deeply to return the economy and monetary system to a usury-free system. This research uses a mixed method with a systematic literature review (SLR) method to identify, evaluate, and synthesize the findings of various studies regarding questions or research topics surrounding fractional reserves, their macroeconomic impact, and solutions from the perspective of Sharia banks. The quantitative approach is also used to support the counting of money multiplier effect. We suggest the consequence of requiring scheme and product development in Sharia banks, one of which is an investment banking scheme with a Mudharabah Muqayyadah product